The rhombic honeycomb – a new mode of self-assembly in liquid crystalline soft matter. Issue 50 (1st June 2022) - Saeed, Azhar; Poppe, Marco; Wagner, Matthias B.; Hauche, Sebastian; Anders, Christian; Cao, Yu; Zhang, Lei; Tschierske, Carsten; Liu, Feng
Abstract : Self-assembly of rod-like molecules with sticky ends (blue) and lateral chains (red) depending on chain volume and strength of core-chain segregation, forms honeycombs with triangular ( p 6 mm ), rectangular ( c 2 mm ), and square ( p 4 mm ) cells. Abstract : Rod-like liquid crystalline (LC) polyphilic compounds with a linear oligo(phenyleneethynylene) core, sticky glycerol groups at each end and two long alkyl side chains (C20 –C32 ) at opposite sides form rhombic honeycombs with inner angles around 60/120°, occurring between triangular and square tiling patterns.